Gawad Parangal ng Kapisanan ng mga Propesor sa Pilipino (KAPPIL) - Gonzalez, Andrew B., FSC (Animo Repository, 1989)
DLSU was among the institutions awarded the Gawad Parangal ng Kapisanan ng mga Propesor sa Pilipino (KAPPIL) at the Philippine Normal College Library. Bro. Andrew Gonzalez, FSC received the award on behalf of the University. Efren Abueg of the Literature Department is KAPPIL's Board Chairman.